2017
DOI: 10.1038/ajg.2016.500
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Gastrostomy Device for the Treatment of Class II and Class III Obesity: Results of a Randomized Controlled Trial

Abstract: Objectives:The AspireAssist System (AspireAssist) is an endoscopic weight loss device that is comprised of an endoscopically placed percutaneous gastrostomy tube and an external device to facilitate drainage of about 30% of the calories consumed in a meal, in conjunction with lifestyle (diet and exercise) counseling.Methods:In this 52-week clinical trial, 207 participants with a body-mass index (BMI) of 35.0–55.0 kg/m2 were randomly assigned in a 2:1 ratio to treatment with AspireAssist plus Lifestyle Counseli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
111
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(115 citation statements)
references
References 17 publications
2
111
0
2
Order By: Relevance
“…In a 52‐week clinical trial by Thompson et al mean (±SD) TBWL was reported to be 12.1 ± 9.6% in the aspiration therapy group, compared with 3.5 ± 6.0% in the control group receiving lifestyle intervention alone ( P < 0.001). With regard to cardiometabolic risk factors, a clinically significant improvement in HbA1c, triglycerides, and high‐density lipoprotein was observed in this pivotal trial, with a modest decrease in low‐density lipoprotein and blood pressure compared with the control group . In one Swedish study, three of five patients with type 2 diabetes (T2D) were able to decrease or completely eliminate medical therapy while using aspiration therapy for 6 months …”
Section: Non‐space‐occupying Therapiesmentioning
confidence: 97%
See 3 more Smart Citations
“…In a 52‐week clinical trial by Thompson et al mean (±SD) TBWL was reported to be 12.1 ± 9.6% in the aspiration therapy group, compared with 3.5 ± 6.0% in the control group receiving lifestyle intervention alone ( P < 0.001). With regard to cardiometabolic risk factors, a clinically significant improvement in HbA1c, triglycerides, and high‐density lipoprotein was observed in this pivotal trial, with a modest decrease in low‐density lipoprotein and blood pressure compared with the control group . In one Swedish study, three of five patients with type 2 diabetes (T2D) were able to decrease or completely eliminate medical therapy while using aspiration therapy for 6 months …”
Section: Non‐space‐occupying Therapiesmentioning
confidence: 97%
“…It is FDA approved for adults aged ≥22 years with a BMI of 35.0 to 55.0 kg/m 2 who have failed to achieve and maintain weight loss with non‐surgical therapy. Two studies conducted in the US have demonstrated that aspiration therapy is safe and effective for long‐term use and results in more weight loss than lifestyle intervention alone . In a 52‐week clinical trial by Thompson et al mean (±SD) TBWL was reported to be 12.1 ± 9.6% in the aspiration therapy group, compared with 3.5 ± 6.0% in the control group receiving lifestyle intervention alone ( P < 0.001).…”
Section: Non‐space‐occupying Therapiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Data from the pivotal trial that led to eventual FDA approval for the AT system were a 52‐week randomized controlled trial of 207 subjects with a BMI of 35–55.0 kg/m 2 49 . Subjects were randomized in a 2:1 ratio to AT plus lifestyle treatment (n = 137) versus lifestyle alone (n = 70).…”
Section: At Systemmentioning
confidence: 99%